Sylvie Blum-Reid. Traveling in French Cinema. New York: Palgrave Macmillan, 2016. - Anne V. Cirella-Urrutia (Studies in 20th & 21st Century Literature, 2018)
Review of Sylvie Blum-Reid. Traveling in French Cinema. New York: Palgrave Macmillan, 2016. viii + 237 pp.
Keywords: Sylvie Blum-Reid; travel; French cinema